1985
DOI: 10.1002/tcm.1770050602
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metabolic cooperation by the anticonvulsants, diphenylhydantoin and phenobarbital

Abstract: High densities of 6-thioguanine-sensitive Chinese hamster V79 cells reduce the recovery of co-cultured 6-thioguanine-resistant cells through a form of intercellular communication (metabolic cooperation). Diphenylhydantoin and phenobarbital, suspected human and animal teratogens and tumor promoters, were able to inhibit intercellular communication at noncytotoxic doses. A potentiation was observed when a mixture of the two chemicals was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Stock solutions of phenytoin (50 mM) were prepared in 100% ethanol (cf. Jone et al, 1985) and diluted in DMEM to final concentrations. Cell cultures were maintained at 37°C in an atmosphere of 94% air and 6% CO,.…”
Section: Introductionmentioning
confidence: 99%
“…Stock solutions of phenytoin (50 mM) were prepared in 100% ethanol (cf. Jone et al, 1985) and diluted in DMEM to final concentrations. Cell cultures were maintained at 37°C in an atmosphere of 94% air and 6% CO,.…”
Section: Introductionmentioning
confidence: 99%
“…Phenobarbital inhibited intercellular communication between Chinese hamster V79 cells (Jone et al, 1986) and between primary cultured rat hepatocytes and ARL liver epithelial cells (Williams, 1980(Williams, , 1981. In contrast, Umeda et al (1980) reported no effect of phenobarbital on intercellular communication between V79 cells.…”
Section: Discussionmentioning
confidence: 94%